PENGARUH PENERAPAN NILAI-NILAI ISLAM DAN KOMITMEN TERHADAP ETOS KERJA DAN DAMPAKNYA KEPADA KUALITAS SUMBER DAYA MANUSIA DI LINGKUNGAN PEMERINTAH KABUPATEN TASIKMALAYA - Sulaeman, Maman (Jurnal Ekonomi & Studi Pembangunan, 2016)
The objectives of the research were to know and to analyze the influence of religious value and commitment application to work ethos and their impact to human resources quality in the Government City of Tasikmalaya. The research method used survey method. The data gathering used questionnaires and library study. The population in this research was 8984 Civil Servants in the Government City of Tasikmalaya. The sample of this research used proportional random sampling. By using path analysis, the study found that religious values, commitment, and work ethos have a significant impact to work quality. Simultaneously, religious value, commitment and work ethos have a significant impact to work quality, so the hypothesis was verified.